DEVELOPMENT OF DIGITAL COMIC LEARNING MEDIA IN ECONOMIC SUBJECTS FOR SENIOR HIGH SCHOOL GRADE 10 - Salsabila, Shafira Salwa; Permatasari, Carolina Lita (Universitas Pelita Harapan, 2023)
ABSTRACTThis study aims to produce digital learning media in the form of digital comics for economics subjects in senior high school grade 10 and equivalent to Demand and Supply subjects. The type of this research is development research. The research procedure uses the ADDIE model, which consists of five stages, including identification (analysis) stage, design stage, development stage, implementation stage, and evaluation stage. The software used in the development of digital comic media is Canva. Based on the results obtained, it can be concluded that economics learning, especially Demand and Supply materials based on digital comics is considered interesting and feasible to apply. This is proven by the results of the validation test of material experts, technological experts, and trials to 40 students who are in the good category. The average on the material expert validation test shows a good category with a score of 4.25. Technological experts indicate the category is quite good with a score of 3.75 while the trials on students were in the good category with a score of 4.0. BAHASA INDONESIA ABSTRAKPenelitian ini bertujuan untuk menghasilkan media pembelajaran digital berupa komik digital untuk mata pelajaran ekonomi kelas 10 SMA dan setara dengan mata pelajaran Permintaan dan Penawaran. Jenis penelitian ini adalah penelitian pengembangan. Prosedur penelitian menggunakan model ADDIE yang terdiridari lima tahap, meliputi tahap identifikasi (analisis), tahap desain, tahap pengembangan, tahap implementasi, dan tahap evaluasi. Perangkat lunak yang digunakan dalam pengembangan media komik digital adalah Canva. Berdasarkan hasil yang diperoleh, dapat disimpulkan bahwa pembelajaran ekonomi khususnya materi Permintaan dan Penawaran berbasis komik digital dinilai menarik dan layak untuk diterapkan. Hal ini dibuktikan dengan hasil uji validasi ahli materi, ahli teknologi, dan uji coba kepada 40 siswa yang berada pada kategori baik. Rata-rata pada uji validasi ahli materi menunjukkan kategori baik dengan skor 4,25. Pakar teknologi menunjukkan kategori cukup baik dengan skor 3,75, sedangkan uji coba pada siswa berada pada kategori baik dengan skor 4.0.